Implementation of Curriculum Management in Improving the Quality of Education at the Integrated Islamic Elementary School in South Tangerang - Nadjematul Faizah (STAI Hubbulwathan Duri, 2023)
The aim of the research is to analyze and describe curriculum management, the impacts challenges and opportunities faced by Integrated Islamic Elementary School in implementing curriculum management. The research method is qualitative through a case study approach. Data gathering methods include conducting interviews with various stakeholders such as school principals, religious teachers, class teachers, administrative staff, students, and parents. Additionally, documentation and observation approaches are employed. Methods for data processing include reduction, display, and drawing conclusions. Data validity strategies encompass credibility through the utilisation of source and technique triangulation, as well as confirmability. The findings of the study indicate (1) Management of the curriculum: (a) Planning: Organising annual meetings and school work meetings. (b) Implementation: Inculcating religious ideals through extracurricular activities by studying iqra', tauhid values, and moral principles. Co-curricular activities involve engaging in collective recitation and communal prayer. Engaging in extracurricular activities like tahfidz (Quran memorization) and da'i (Islamic preaching). (c) Evaluation: School principals assess curriculum performance through supervision and observation, while teachers review and enhance it by assigning tasks, conducting examinations, and holding mid-term exams and end-of-semester meetings. (2) Impact: Student academic performance improves, pupils develop a strong Islamic character, and the learning process is successful. The constraints include a lack of financial resources for teacher training and infrastructure, limited time for implementation, and the absence of government policy. Opportunity: enhanced faculty, comprehensive facilities, consistent operational schedule, and transformation into an institution with an Islamic ethos. Conclusion: The management of the curriculum is functioning according to expectations. Recommendation: It is advisable for schools to incorporate community stakeholders, in addition to student guardians, in the process of curriculum preparation.